Clinical characteristics of 144 cases of neonatal acne - Xinjing GAO; Zhuo WANG; Haipian LI (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2021)
Objective: To explore the clinical characteristics of neonatal acne. Methods: 144 patients of neonatal acne from 2018.6 to 2018.12 were studied in this study. Results: A total of 144 cases were collected, including 107 males (74.31%) and 37 females (25.69%), 94 cases (65.28%) of normal delivery. The average age of onset was 19.6 days. 84 cases (58.33%) were exclusively breast-fed, 32 cases (22.22%) were fed with formula milk, and 28 cases (19.44%) were mixed-fed. One or both parents of 114 cases (79.17%) had a history of acne, and 25 cases (17.36%) were serious. There were 27 cases (18.75%) with acne atrophic scars, in which 25 parents with a history of acne, and 6 severe. Children with at least one parent with a history of acne are more likely to leave scars after infant acne (χ2=0.01, P<0.01). Among them, if the parents have a history of severe acne, their children are more likely to leave scars (χ2=0.03, P<0.01). There were 9 cases with white skin, 8 cases with black skin, and 10 cases with moderate skin color. Conclusion: Neonatal acne is easy to be misdiagnosed. If parents have a history of adolescent acne, especially severe cases, their children are more likely to leave scars. Clinicians should raise awareness, help children and parents better prevent and treat acne and scar.